1996
DOI: 10.1038/382816a0
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of the tumour suppressors IRF-1 and p53 in response to DNA damage

Abstract: Normally growing cells promptly cease DNA synthesis when exposed to genotoxic stresses, such as radiation, and this cell-cycle arrest prevents the accumulation of mutations. The transcription factor interferon regulatory factor (IRF)-1 is essential for the regulation of the interferon system, inhibits cell growth, and manifests tumour-suppressor activities. Here we show that mouse embryonic fibroblasts (EFs) lacking IRF-1 are deficient in their ability to undergo DNA-damage-induced cell-cycle arrest. A similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
275
1
5

Year Published

1997
1997
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 320 publications
(298 citation statements)
references
References 26 publications
15
275
1
5
Order By: Relevance
“…Although BAX expression is not modulated during the combined activation of HER1 and IRF-1 (data not shown) the experiments demonstrate a further similarity between IRF-1 and p53. It has been reported earlier that both tumor suppressor proteins cooperate in response to DNA damage (Tamura et al, 1995;Tanaka et al, 1996).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Although BAX expression is not modulated during the combined activation of HER1 and IRF-1 (data not shown) the experiments demonstrate a further similarity between IRF-1 and p53. It has been reported earlier that both tumor suppressor proteins cooperate in response to DNA damage (Tamura et al, 1995;Tanaka et al, 1996).…”
Section: Discussionmentioning
confidence: 95%
“…The principle of synergistic action of transcription factors with IRF-1 is quite common; IRF-1 has been shown to cooperatively interact with TFIIB (Wang et al, 1996); NF-kB (Drew et al, 1995), and STAT1 (Chon et al, 1996). It is also described that IRF-1 together with p53 induces the cell cycle inhibitor p21 (Tanaka et al, 1996). However, so far we were not able to detect a direct interaction of IRF-1 with one of the STAT proteins, neither by gel retardation nor by a two hybrid system in mammalian cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that IRF7/7 MEFs are de®cient in their ability to undergo DNA-damageinduced cell-cycle arrest (Tanaka et al, 1996). Transcriptional activation of the cyclin dependent kinase inhibitor (CDKI) p21 gene in these cells by irradiation, was found to be dependent both on p53 and IRF-1.…”
Section: Terminal DI Erentiation Negative Growth Control and Myd Genesmentioning
confidence: 99%